2015
DOI: 10.1007/s11606-015-3362-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Care Transition Intervention on the Patient Experience of Older Multi-Lingual Adults in the Safety Net: Results of a Randomized Controlled Trial

Abstract: An inpatient standalone transition-of-care intervention did not improve patient discharge experience. Older multi-lingual and cognitively impaired populations may require higher-intensity interventions post-hospitalization to improve discharge experience outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 41 publications
5
56
1
1
Order By: Relevance
“…Another pre-post assessment of a communication skills training programme for hospitalists also did not improve Communication with Doctors or Overall Hospital Rating 7. A randomised controlled trial for a nurse-led, language-concordant, hospital-based care transition programme that did not improve any of the Communication domains or Discharge Information domains;13 similarly, a pre-post assessment of changing care management from a unit-based model to a service-based one did not affect HCAHPS score for Recommend the Hospital 9. Finally, two studies did not report p values.…”
Section: Resultsmentioning
confidence: 99%
“…Another pre-post assessment of a communication skills training programme for hospitalists also did not improve Communication with Doctors or Overall Hospital Rating 7. A randomised controlled trial for a nurse-led, language-concordant, hospital-based care transition programme that did not improve any of the Communication domains or Discharge Information domains;13 similarly, a pre-post assessment of changing care management from a unit-based model to a service-based one did not affect HCAHPS score for Recommend the Hospital 9. Finally, two studies did not report p values.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, during planning and performance of transitional care, effective communication between the elderly/family and the health professional is essential, so that failures in this stage do not result in re-hospitalizations. Efficient communication is based on planning, which aims at continuing education for the elderly and their family in the context of treatment, maintenance of medication and guidance of support networks, allowing a better experience after discharge, reducing the burden at home (22) .…”
Section: A24mentioning
confidence: 99%
“…It is also up to the professional to work through home visits two weeks after leaving. This type of care assesses the impact of adequate planning on discharge (22) .…”
Section: A24mentioning
confidence: 99%
See 1 more Smart Citation
“…One factor Chan et al do not address is social support. 2 A similar article with a negative intervention result 3 found that social support may be a key factor in determining patient readiness to accept and use intervention help.…”
mentioning
confidence: 99%